A Step-by-Step Guide to Double-Puncture Technique for Endoscopic Management of Ureterocele - Nabavizadeh, Behnam; Nabavizadeh, Reza; Kajbafzadeh, Abdol-Mohammad (Urology Journal, 2024)
To date, the optimal surgical technique for treatment of ureterocele remains unclear and the available options are variable. The endoscopic techniques that are gaining popularity mostly share major drawbacks including low success rate, high probability of mandatory secondary surgery and de novo vesicoureteral reflux to the ureterocele moiety. The Double-Puncture technique is shown to have promising outcomes in terms of long-term success and low rate of complications. In this video, a step-by-step guide to this technique is presented.